Review paperThe using of biological agents in dermatology - Pełka, Marcin; Broniarczyk-Dyła, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Judging from medical publications from recent years one can notice that modern biological agents have become more and more popular as therapeutic options for many diseases. So far they were successfully implemented in different oncological, endocrinological and rheumatological disorders. Numerous publications describe the use of biologicals in dermatology. The most measurable experiences and observations are connected with difficult cases of psoriasis and arthropatic psoriasis. Single publications indicate the profits from using biologicals in bullous diseases, alopecia areata, pyodermia gangrenosum, dermatitis atopica and other skin disorders. This article is a survey of the opinions of the efficacy and safety of biological agents and the possibilities for broadening the therapeutic options in dermatology.